A good and wise measure : the search for the Canadian-American boundary, 1783-1842 - Carroll, Francis M. (Professor) (University of Toronto Press, 2001)
The story of the attempts to settle the original boundary between British North America and the United States. Though established by the Treaty of Paris in 1783, the boundary was plagued by ambiguities and errors in the document.